2007
DOI: 10.1021/ja068881i
|View full text |Cite
|
Sign up to set email alerts
|

Infrared and Ultraviolet Spectral Signatures and Conformational Preferences of Jet-Cooled Serotonin

Abstract: The ultraviolet and infrared spectroscopy of single conformations of neutral serotonin (5-hydroxytryptamine) have been studied in the gas phase using a combination of methods including laser-induced fluorescence, resonance-enhanced two-photon ionization, UV-UV hole-burning spectroscopy, and resonant ion-dip infrared spectroscopy. By comparison to its close analogue tryptamine, for which firm assignments to seven low-energy conformations have been made, UV and IR transitions due to eight conformations of seroto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
114
1
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(132 citation statements)
references
References 50 publications
(122 reference statements)
15
114
1
2
Order By: Relevance
“…LeGreve et al [26] have proposed eight conformational isomers of serotonin while the same authors [34] have suggested that serotonin exist in 13 conformations. Cabezas et al [35] have found only three conformers from microwave spectroscopy.…”
Section: Experimental and Computational Detailsmentioning
confidence: 99%
See 2 more Smart Citations
“…LeGreve et al [26] have proposed eight conformational isomers of serotonin while the same authors [34] have suggested that serotonin exist in 13 conformations. Cabezas et al [35] have found only three conformers from microwave spectroscopy.…”
Section: Experimental and Computational Detailsmentioning
confidence: 99%
“…LeGreve et al [26] have studied the ultraviolet and IR spectra of single conformation of neutral serotonin in the gas phase. Mouric and Emson [24] have carried out theoretical conformational study of serotonin and assigned calculated frequencies for the conformers only in the region 2800e3000 cm À1 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been a lot of experimental and theoretical studies on multiconformer biomolecular systems in gas phase [1][2][3][4][5]. Among all the neurotransmitters serotonin has been studied extensively whose flexible ethylamine chain has attracted the most for the quantum chemical investigations.…”
Section: Introductionmentioning
confidence: 99%
“…The stability of different conformers of serotonin is determined by the interaction of ethylamine chain with aromatic p-electron density [4,5]. The interest in the conformational studies on these large flexible biomolecules has been enhanced by the growing accuracy of quantum mechanical calculations.…”
Section: Introductionmentioning
confidence: 99%